Mission schools as seedbed for social transformation: Lessons drawn from the Methodist Church - Peter Masvotore (HTS Teologiese Studies/Theological Studies)
In Africa, and in Zimbabwe in particular, education has played a critical role in transforming society through missionaries who brought education as inseparable from Christianity. This article argues that mission school education was a pillar of transformation and that mission schools functioned as centres of integration facilitation where learners discovered how to contribute in the change of their biosphere. It further argues that Zimbabwean mission schools are still bearing fruit in various contexts as seedbeds of social transformation. For Zimbabwe, education was and is still the hub of social transformation. Using a desk research approach of historical analysis and participant observation, this article explores how Zimbabwean Methodism transforms society by remaining within the academic niche that continues to facilitate societal transformation. It also discusses how the Methodist Church in Zimbabwe (MCZ) has influenced universal transformation processes through mission schools. The article concludes that mission schools are positive contributors to social transformation in Zimbabwe today, and that no transformation can be argued to have taken place without them.